2014
DOI: 10.1142/s0217979214300151
|View full text |Cite|
|
Sign up to set email alerts
|

Critical phenomena in one dimension from a Bethe ansatz perspective

Abstract: This article briefly reviews recent theoretical developments in quantum critical phenomena in one-dimensional (1D) integrable quantum gases of cold atoms. We present a discussion on quantum phase transitions, universal thermodynamics, scaling functions and correlations for a few prototypical exactly solved models, such as the Lieb-Liniger Bose gas, the spin-1 Bose gas with antiferromagnetic spin-spin interaction, the two-component interacting Fermi gas as well as spin-3/2 Fermi gases. We demonstrate that their… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 199 publications
(309 reference statements)
1
15
0
Order By: Relevance
“…5-6 we report the temperature dependence of the chemical potential of the system described by Hamiltonian (1) as obtained numerically from the Bethe-ansatz (BA) approach first developed by Yang-Yang [5][6][7]23] for several characteristic values of γ. The Yang-Yang description has been probed experimentally [24,25] and allows not only to investigate the thermodynamics, but also the Luttinger liquid physics and the quantum criticality of the system [26][27][28]. The numerical results for the thermodynamics have been derived recently in an analytic fashion by using the polylog functions at finite temperature by Guan and Batchelor [26,28].…”
Section: Low-temperature Expansion Of the Chemical Potentialmentioning
confidence: 99%
“…5-6 we report the temperature dependence of the chemical potential of the system described by Hamiltonian (1) as obtained numerically from the Bethe-ansatz (BA) approach first developed by Yang-Yang [5][6][7]23] for several characteristic values of γ. The Yang-Yang description has been probed experimentally [24,25] and allows not only to investigate the thermodynamics, but also the Luttinger liquid physics and the quantum criticality of the system [26][27][28]. The numerical results for the thermodynamics have been derived recently in an analytic fashion by using the polylog functions at finite temperature by Guan and Batchelor [26,28].…”
Section: Low-temperature Expansion Of the Chemical Potentialmentioning
confidence: 99%
“…In this system, R W also depends on the temperature. Recently the effect of the polarization on the Wilson ratio of Fermi gases in 1D has been studied [34][35][36] . It is found that R W exhibits anomalous enhancement at critical points.…”
Section: Resultsmentioning
confidence: 99%
“…This method, however, is restricted to uniform systems in the ground state (or close to it [37,38]). Finitetemperature analyses require the thermodynamic Bethe ansatz, which involves solving an infinite tower of coupled nonlinear integral equations [37,38], which leads to potentially uncontrolled approximations [39][40][41][42][43][44][45]. The Monte Carlo techniques used here, on the other hand, have well-controlled systematic and statistical uncertainties.…”
Section: Discussionmentioning
confidence: 99%